2009
DOI: 10.5194/acp-9-3721-2009
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary contributions to aerosol light scattering and absorption in Mexico City during the MILAGRO 2006 campaign

Abstract: Abstract.A photoacoustic spectrometer, a nephelometer, an aethalometer, and an aerosol mass spectrometer were used to measure at ground level real-time aerosol light absorption, scattering, and chemistry at an urban site located in North East Mexico City (Instituto Mexicano del Petroleo, Mexican Petroleum Institute, denoted by IMP), as part of the Megacity Impact on Regional and Global Environments field experiment, MILAGRO, in March 2006. Photoacoustic and reciprocal nephelometer measurements at 532 nm accomp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
51
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 53 publications
17
51
3
Order By: Relevance
“…During temperature inversion periods, the local health officials of Washoe County, Nevada announced air pollution alerts to encourage inhabitants to refrain from extended outdoor activities, and banned residential wood burning (see, http://www.co.washoe.nv.us/ repository/print pr.php?article=8510). The β abs during these conditions was comparable to that of Reno, NV during the California wild fire season in the summer of 2008 and to that in Mexico City (Gyawali et al, 2009;Paredes-Miranda et al, 2009). Figure 3 presents the aerosol time-series of β sca and β abs at 355 nm in conjunction with meteorological parameters from two near surface stations in Reno separated by an altitude difference of 143 m. Figure 3a and b display the temperature gradient normalized by the dry adiabatic lapse rate (−9.8 • C km −1 ) and the wind speed, respectively.…”
Section: Calculation Ofångström Exponent Of Absorption (Aea) Angströmentioning
confidence: 58%
“…During temperature inversion periods, the local health officials of Washoe County, Nevada announced air pollution alerts to encourage inhabitants to refrain from extended outdoor activities, and banned residential wood burning (see, http://www.co.washoe.nv.us/ repository/print pr.php?article=8510). The β abs during these conditions was comparable to that of Reno, NV during the California wild fire season in the summer of 2008 and to that in Mexico City (Gyawali et al, 2009;Paredes-Miranda et al, 2009). Figure 3 presents the aerosol time-series of β sca and β abs at 355 nm in conjunction with meteorological parameters from two near surface stations in Reno separated by an altitude difference of 143 m. Figure 3a and b display the temperature gradient normalized by the dry adiabatic lapse rate (−9.8 • C km −1 ) and the wind speed, respectively.…”
Section: Calculation Ofångström Exponent Of Absorption (Aea) Angströmentioning
confidence: 58%
“…The HR-AMS reported size distribution for chemical species vs. vacuum aerodynamic diameter (D va ;DeCarlo et al, 2004), from which volume equivalent diameter (D ve ) was estimated assuming sphericity and using the estimated sizeresolved density (as discussed below). The instrumental intercomparisons and main results of the HR-AMS in this study have been reported in previous publications (Aiken et al, 2008Paredes-Miranda et al, 2009;Huffman et al, 2009;Salcedo et al, 2010;Cappa and Jimenez, 2010) The AMS reported non-refractory inorganic species (sulfate, nitrate, ammonium, and chloride) as well as total organic aerosol (OA). The OA measured by the AMS was classified into different components using Positive Matrix Factorization (Paatero, 1997;Ulbrich et al, 2009) of the highresolution OA spectra, as described by Aiken et al (2009).…”
Section: Aerosol Chemical Compositionmentioning
confidence: 99%
“…Additional information on the chemical and physical characteristics of emissions from mobile sources has been obtained from source apportionment analysis of stationary data at T0 Paredes-Miranda et al, 2009), area-averaged emission fluxes at the SIMAT tower Notes: a NO x (expressed as NO 2 ) emissions in the inventory were assumed 90% NO and 10% NO 2 in mass. b Total VOCs emissions from the inventory include evaporative emissions.…”
Section: Mobile Emissions Measurementsmentioning
confidence: 99%